Chilled Storage Study of Value Added Black Clam (Villorita cyprinoides) (Gray, 1825) products in two different Packaging Materials - Anju, A. V.; Harsha, K.; Sethulakshmi, C. S.; Sreejith, S.; Panda, Satyen Kumar; Gopal, Nikita; Bindu, J. (Fishery Technology, 2019)
Black clam (Villorita cyprinoides) (Gray, 1825), a nutrient rich bivalve was used for preparing two products viz., clam cutlet and clam bonda, and packaged in two different packaging materials, 200 gauge low density polyethylene and 12 Âµ polyester/ 200 gauge polyethylene laminate. The biochemical and microbiological parameters of the products were analyzed to study its storage stability in chilled condition. Parameters like pH, color (L*, a*, b*), total volatile base nitrogen (TVBN), thiobarbituric acid (TBA), peroxide value (PV) and free fatty acid (FFA) were within permissible limit during the period of observation. The aerobic plate count, after 24 days of storage of the products were in the range of 6.81 to 7.41 log10 cfu g-1 and 6.3 to 7 log10 cfu g-1 for LDPE and PES/PE respectively. Escherichia coli and Enterobacteriaceae were absent throughout the storage period. The study showed that biochemical and microbiological parameters were greater for the products packed in LDPE compared to PES/PE laminate, indicating that the laminate film was more efficient in preserving the quality of the products when compared to monolayer films.